2016
DOI: 10.1002/chem.201600894
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Well‐Dispersed Pt Nanoparticles in Mesoporous Silica with Large Open Spaces and Their Catalytic Applications

Abstract: In this paper, a facile strategy is reported for the preparation of well-dispersed Pt nanoparticles in ordered mesoporous silica (Pt@OMS) by using a hybrid mesoporous phenolic resin-silica nanocomposite as the parent material. The phenolic resin polymer is proposed herein to be the key in preventing the aggregation of Pt nanoparticles during their formation process and making contributions both to enhance the surface area and enlarge the pore size of the support. The Pt@OMS proves to be a highly active and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Figure shows the catalytic performance of the Pt/Al 2 O 3 membranes for CO oxidation. The membrane with 1 wt % Pt content was chosen as the representative membrane because it has the usual Pt loading amount for CO oxidation. , Notably, the membrane was used directly without trituration or mixing with quartz sand. The trituration and mixture with quartz sand process is usually used for the powder-form catalysts to enhance dispersion. ,, Figure a shows the results of CO conversion as a function of the reaction temperature.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Figure shows the catalytic performance of the Pt/Al 2 O 3 membranes for CO oxidation. The membrane with 1 wt % Pt content was chosen as the representative membrane because it has the usual Pt loading amount for CO oxidation. , Notably, the membrane was used directly without trituration or mixing with quartz sand. The trituration and mixture with quartz sand process is usually used for the powder-form catalysts to enhance dispersion. ,, Figure a shows the results of CO conversion as a function of the reaction temperature.…”
Section: Resultsmentioning
confidence: 92%
“…The Pt crystal sizes were 2.7, 6.5, 8.2, and 26.2 nm when the membranes were calcined at 500, 600, 700, and 800 °C, respectively. It was reported that the nanosized Pt particles show excellent catalytic performance, , and that the catalytic performance is inversely correlated with the particle size . Therefore, the membranes calcined at 500 °C should show excellent catalytic performance characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear dependence of ln (A t /A 0 )v ersusr eaction t (Figure 12 c) for Pt@CF-12 clearly indicated that the reaction followed pseudo-first-orderb ehavior.T he rate constants k were calculated from the slopeso ft he plots and determined to be 4.1 10 À3 and 1.8 10 À3 s À1 for Pt@CF-12 and Pt@F-12, respectively,w hicha re similar to those of Pt-basedc atalysts on variouss ilica supports presented in Ta ble 3f or the same reaction. [66][67][68][69][70] The Pt@CF-12 and Pt@F-12 catalysts can convert 93 and 81 %o f4 -nitrophenol to 4-aminophenol, respectively,a fter 10 min. The higher catalytic activity of Pt@CF-12 compared with Pt@F-12 couldbeascribed to the smaller size and uniform distribution of Pt NPs in the cage-type mesopores.…”
Section: Catalytic Activities Of Pt@f-12 and Pt@cf-12f Or Ab Hydrolysmentioning
confidence: 99%
“…The apparent rate constant was calculated from the slope to be 5.57 Â 10 À3 s À1 , comparable or higher than previously reported values. [26][27][28] The Pt/ZIF/MNC nanoparticles were magnetically collected and used for subsequent reactions to examine if the catalytic activity of Pt was maintained. Fig.…”
Section: Catalytic Activity Of Pt/zif/mncmentioning
confidence: 99%